PENGARUH DEBT TO EQUITY RATIO DAN TOTAL ASSETS TURNOVER TERHADAP NET PROFIT MARGIN PADA PT MAYORA INDAH Tbk PERIODE 2013-2023 - Maulida Fatichatur Rizqiyah; Ferdina Watiningsih (Journal of Research and Publication Innovation, 2025)
This research aims to determine whether there is a significant influence between Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) on Net Profit Margin (NPM) at PT Mayora Indah Tbk for the 2013-2023 period, either partially or simultaneously. The method used in this research is a quantitative descriptive research method, using secondary data from the financial reports of PT Mayora Indah Tbk for the 2013-2023 period. Based on partial research results, the Debt to Equity Ratio (DER) does not have significant influence on the Net Profit Margin (NPM) at PT Mayora Indah Tbk. This can be proven from the results of the tcount value of -1.442 < ttable of 2.306 with a significant value of 0.187 where the value is 0.187 > 0.05. Partially Total Assets Turnover (TATO) has no significant  influence on Net Profit Margin (NPM) at PT Mayora Indah Tbk. This can be proven from the results of the tcount value of -2.130 < t table 2.306 with a significant value of 0.066 where the value is 0.066 > 0.05. Simultaneously, the Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) have no significant influence on the Net Profit Margin (NPM) at PT Mayora Indah Tbk. This can be proven from the results of the Fcount value of 2.998 < Ftable value of 4,46 with a significant value of 0.107 where the value is 0.107 > 0.05. The R Square value was 28.6%, while 71.4% was accounted for by other variables not examined in this study